The collaborative exploration of alternative futures: A different appr oach to Theories of Change (CEDIL programme, 2022)
ParEvo is a web application that enables the collaborative constructio n and exploration of a range of alternative futures: likely and unlike ly, desirable and undesirable. These are described in the form of a br anching narrative structure, developed over a series of iterations inv olving the interactions of a group of participants. These detailed sto rylines about the future contrast with optimistic, skeletal and largel y singular views of the future found in diagrammatic ToCs often encoun tered by evaluators. This webinar will describe a recent ParEvo exerci se implemented by the Centre for the Study of Existential Risk (CSER) in Cambridge. In this exercise 11 international experts explored ideas about how global risks associated with biotechnology research could b e managed, and mismanaged, in the coming four years. Including how the se alternative futures were evaluated by participants and the CSER fac ilitators. Issues to be discussed by the panel, and others, include co mparisons with other representations of Theories of Change and other a pproaches to the exploration of alternative futures, described various ly as scenario planning, futures or foresight work. Speakers: Rick Dav ies, Lara Mani Tom Hobson An overview of the app can be found here: ht tps://mscinnovations.wordpress.com/ The app website is here: https://p arevo.org/